SOCIAL AND POLITICAL SITUATION IN SAMTSKHE-JAVAKHETIA AND AROUND IT - GOGORISHVILI, Nugzar (CENTRAL ASIA AND THE CAUCASUS, 2006)
The Southern Caucasus is not merely the crossroads of the North-South and EastWest transportation and communication routes. It is the place where the ambitions of the most influential actors—Russia, Western Europe and America—clash.For various reasons, Russia is obviously the most influential regional force, its impact is felt in Georgia’s Samtskhe-Javakhetia region in particular, therefore the situation there should be considered in the context of Russia’s influence.Over the past ten years, Samtskhe-Javakhetia has been repeatedly discussed by politicians, state and public figures, as well as all kinds of experts. The region figured in numerous official state and interstate as well as public projects designed to carry out sociological research there, improve its social and economic infrastructure, and remedy other local ills. Tens of millions of U.S. dollars supplied by all sorts of international organizations (the EU, Council of Europe, OSCE) and local and international foundations based in the U.K., Germany, and the U.S. were poured into these efforts.Today, however, no one can say that the state and the public sector have achieved concrete results: just like back in the 1990s, the local people are still complaining about social and economic problems and feel abandoned by the Georgian central authorities and the international community as a whole. The local public leaders have returned to the political slogans of the past, which became even more radical than before.In fact, the agreement between the governments of Georgia and the Russian Federation on the Russian military base in Akhalkalaki is the only tangible result: on the strength of the November 1999 decisions of the OSCE Istanbul summit, Russia began removing its military hardware from the base.It should be said that the local realities are rarely discussed: each of the sides involved tends to use the media to promote its own ideas and the methods to be employed. It is very hard to say whether they have anything to do with the region’s public opinion.